Exploring the backward swimming ability of a robotic fish: Combining modelling and experiments. (4th October 2016) - Li, Liang; Wang, Chen; Fan, Ruifeng; Xie, Guangming
This article investigates the capability for backward swimming of a carangiform-fish-like robot with only three joints. A simple dynamic model based on a fixed point, a point in the body without perpendicular oscillation, is first developed to analyze the feasibility of backward motion for the robot. Through this theoretical analysis, we find that the fixed point lies closer to the robotic fish tail with higher backward swimming speeds. Combining the theoretical analysis with experimental optimization, we further explore backward swimming patterns using particle swarm optimization. After a series of online optimal experiments, we find several locomotion gaits that can make the robotic fish swim backward, and the corresponding fixed points are similarly located near the tail. The backward swimming velocity is strongly correlated with the fixed point position along the robotic fish body, which verifies the effectiveness of our fixed-point model.